Analisis Preferensi Konsumen Produk Keripik Tempe di PT Intan Rahmadhani Santosa - Hapsari, Elmi Yudi; Suprihanti, Antik (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2024)
Consumers in making purchases will manage information, look for certain benefits, and look at product attributes. The level of importance of attributes for each consumer is different, which also causes differences in consumer preferences. Analyzing consumer preferences is important to find out the most preferred choice by consumers. The study aims to identify the characteristics of consumers, analyze consumer preferences for tempeh chip attributes, and analyze the attributes most consumers consider in purchasing tempeh chips at PT Intan Rahmadhani Santosa. Respondents determined using purposive as many as 90 consumers of tempeh chips at PT Intan Rahmadhani Santosa. The data analysis techniques used are descriptive analysis and conjoin analysis. The results showed that most consumers are 21-25 years old, from Yogyakarta, have a high school education, are students, and have an income of less than Rp 500,000. Attributes that became the preference of consumers of tempeh chips were the price of less than Rp 15.000, mercon flavor, round chip shape, thin thickness, crispy texture, durability of more than 3 months, weight of 140 grams, and standing pouch packaging. The most consumers considered attribute is price.